Barriers and facilitators to programmatic mass drug administration in persistent schistosomiasis hotspot communities: An ethnographic study along Lake Albert, midwestern Uganda. - Paskari Odoi; Stella Neema; Birgitte J Vennervald; Edridah M Tukahebwa; Shona Wilson (PLoS Neglected Tropical Diseases)
Background The WHO Neglected Tropical Disease Roadmap for 2021-2030 includes the goal of eliminating schistosomiasis as a public health problem in all endemic countries. Despite heightened efforts since 2012, critical action is still required in addressing barriers to Mass Drug Administration, the primary control method. This includes improvement in adherence by the populations in persistent schistosomiasis hotspots. One such hotspot is the shoreline of Lake Albert, Uganda, where schistosomiasis control is provided to school-aged children and adults. An overemphasis on regular treatment, without comprehensively addressing factors that result in low uptake of treatment in these high-risk populations is likely to impact the elimination of schistosomiasis as a public health problem. Methods An ethnographic study using in-depth interviews, key informant interviews, focus group discussions and participant observation was conducted at two study sites along Lake Albert. Thematic content analysis was used during data analysis. Results The study revealed that the size, taste and smell of the drug, along with its side-effects; poor community integration and occupational behaviour resulting in non-mobilisation; and unfounded rumours and beliefs remain reasons for persistent low uptake of praziquantel by some. Conversely, lived experience of improved health through participation and knowledge of the dangers of the disease if not treated, facilitated treatment uptake. Positive attitudes to localised sensitisation by community drug distributors show social influence facilitates crucial knowledge attainment. Treatment uptake is further facilitated by the delivery of the drug at no cost at home. Crucially, for the majority of participants the facilitating factors were found to outweigh the inhibitory factors related to the drug's side effects. Conclusion We recommend a good community engagement strategy that provides continuous education and sensitisation, with improved recruitment and training provision for Community Drug Distributors to facilitate programme reach to groups with current poor engagement.